European Trade, Colonialism and Human Capital Accumulation in Senegal, Gambia and Western Mali, 1770 - 1900 - Gabriele Cappelli; Jörg Baten (Center for Economic Studies and ifo Institute (CESifo), 2017)
We trace the development of human capital in today's Senegal, Gambia, and Western Mali between 1770 and 1900. European trade, slavery and early colonialism were linked to human capital formation, but this connection appears to have been heterogeneous. The contact with the Atlantic slave trade increased regional divergence, as the coast of Senegambia developed more quickly than inner areas. This pattern was affected by French early colonialism and by the reaction of different West African populations to the economic incentives provided by foreign demand for agricultural products. The peanut trade since the mid-19th century further amplified regional economic inequalities.
Keywords: N37; N57; I21; 330; numeracy; West Africa; trade; colonialism